A Study of Natural Disaster 2013 and Tourism Business of Uttarakhand: Exploring the negative impact of natural disasters on tourism business in Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Uttarakhand is called as land of god and acts of god destroy tourism business in the area. Uttarakhand faced disaster continuously throughout history, but 2013 disaster affected a lot to tourism, community and environment. Researcher studied here relationship between natural disaster and tourism business. Results indicate that natural disaster influence tourism business negatively.